Human Rights and Gender Perspective - María Leoba Castañeda Rivas (Revista Facultad de Jurisprudencia, 2021)
Talking about the idea of gender equity throughout history is very complex because this concept only began to emerge in the mid-1970s as a response to the asymmetry and inequality existing between men and women according to their sex. However, to investigate the origin of this idea, we can note the predominance of the male gaze, since, until very recent times, women were never the object of study in history as such.